Copper(II) Pyridyl Aminophenolates: Hypoxia‐Selective, Nucleus‐Targeting Cytotoxins, and Magnetic Resonance Probes. Issue 38 (21st May 2021) - Prosser, Kathleen E.; Xie, Da; Chu, Annica; MacNeil, Gregory A.; Varju, Bryton R.; Kadakia, Rahul T.; Que, Emily L.; Walsby, Charles J.
Abstract: Targeting the low‐oxygen (hypoxic) environments found in many tumours by using redox‐active metal complexes is a strategy that can enhance efficacy and reduce the side effects of chemotherapies. We have developed a series of Cu II complexes with tridentate pyridine aminophenolate‐based ligands for preferential activation in the reduction window provided by hypoxic tissues. Furthermore, ligand functionalization with a pendant CF3 group provides a 19 F spectroscopic handle for magnetic‐resonance studies of redox processes at the metal centre and behaviour in cellular environments. The phenol group in the ligand backbone was substituted at the para position with H, Cl, and NO2 to modulate the reduction potential of the Cu II centre, giving a range of values below the window expected for hypoxic tissues. The NO2 ‐substituted complex, which has the highest reduction potential, showed enhanced cytotoxic selectivity towards HeLa cells grown under hypoxic conditions. Cell death occurs by apoptosis, as determined by analysis of the cell morphology. A combination of 19 F NMR and ICP‐OES indicates localization of the NO2 complex in HeLa cell nuclei and increased cellular accumulation under hypoxia. This correlates with DNA nuclease activity being the likely origin of cytotoxic activity, as demonstrated by cleavage of DNA plasmids in the presence of the Cu II nitro complex and a reducing agent. Selective detection of the paramagnetic Cu II complexes and their diamagnetic ligands by 19 F MRI suggests hypoxia‐targeting theranostic applications by redox activation. Abstract : Fluorine‐labelled Cu II complexes have been developed as hypoxia‐targeting chemotherapeutics and MRI agents. Tuning the electronic properties identified a nitro‐substituted complex as having hypoxia‐selective cytotoxicity driven by nuclear accumulation and DNA cleavage. 19 F magnetic resonance experiments discriminate between Cu II and reduced complexes, thus demonstrating a bifunctional role for Cu II complexes as both hypoxia probes and chemotherapeutic agents.